Internalisasi Nilai-Nilai Pancasila Dalam Mencegah Paham Radikal - Sri Rahayu Pudjiastuti (Jurnal Ilmiah Mimbar Demokrasi, 2020)
This descriptive research aims to contribute thoughts, ideas and strategies and efforts to internalize the values of Pancasila to prevent the development of radical understanding. This writing uses a descriptive method that is seen as a comprehensive integral. The results showed that the current conditions of internalizing Pancasila values were; weak education system, resistance to the ideology of Pancasila, lack of exemplary leaders, and the increasing negative influence of external values that are not in accordance with Pancasila. The internalization of Pancasila values is done by; strengthening the education system, enhancing national identity and character, increasing the commitment of national leaders, increasing understanding of Pancasila values in daily life to increase the deterrence of negative influences through education, outreach and cooperation. This study concludes that the internalization of the values of Pancasila can increase community awareness in counteracting the spread of radical ideas.